ENHANCING SELF-CARE AND PERSONAL HYGIENE SKILLS AMONG STUDENTS OF SMK GEMEREH SEGAMAT, MALAYSIA - Malahayati Rusli Bintang; Silvia Mona; Raymond; Yuanita FD Sidabutar (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This community service project aimed to improve self-care and personal hygiene skills among students of SMK Gemereh Segamat Johor Malaysia. Personal hygiene is a crucial component affecting students' health, confidence, and learning performance. The program was conducted descriptively involving 25 students selected through total sampling. Activities included observation, interviews, pre-test, educational video sessions, and direct demonstrations. Data were collected through questionnaires assessing daily hygiene practices, handwashing habits, nail care, body hygiene, and cleanliness of clothing. The results show that before the program, students demonstrated moderate self-care and hygiene practices, especially in handwashing, nail care, and menstrual hygiene. After the intervention, there was a significant improvement in overall hygiene behavior, with 72% of students categorized as having good personal hygiene and 64% categorized as having adequate self-care. The program successfully enhanced students’ awareness and daily practices regarding cleanliness and health. Further community involvement and continuous monitoring are recommended to sustain behavioral changes.